A disaster diplomacy perspective of acute public health events. (6th August 2018) - Whittaker, Charlie; Frühauf, Anna; Burthem, Samuel John; Parry, Rebecca Shoshanah; Kotikalapudi, Meghana; Liang, Yihui; Barker, Mary Moffett; Patel, Parth Rohit; Kelman, Ilan
Abstract : Conceptions of acute public health events typically assume that they are tackled exclusively or principally through technical and medical solutions. Yet health and politics are inexorably linked. To better understand this link, this paper adopts a disaster diplomacy perspective for analysing and assessing the impacts of acute public health events on diplomatic outcomes. Two gaps in understanding disaster‐health‐politics connections are addressed: (i) how health interventions can impact diplomatic endeavours, especially for (ii) acute public health events. Three diverse case studies are interpreted from a disaster diplomacy perspective: Cuba's medical diplomacy, China and Severe Acute Respiratory Syndrome (SARS), and polio vaccination. Disaster diplomacy permits deeper investigation and analysis of connections amongst health, disaster, and diplomatic activities by viewing efforts on acute public health events as being political through disaster risk reduction (beforehand) and disaster response (during and afterwards). Understanding improves how health interventions affect diplomacy and on disaster diplomacy's limitations.